ANALISIS WACANA PADA PIDATO MARTIN LUTHER KING JR. â€œI HAVE A DREAMâ€. (Addressed to the March on Washington). - TULASEKET, EVIANTRI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â  The research is entitled Discourse Analysis of Martin Luther King Jr.â€™s speech, â€œI Have a Dreamâ€ (Addressed to the March on Washington). It is an attempt to analyzeand explain the discourse analysis norms. The objective of this research is to identify, classify, and analyze the discourse analysis norms in Martin Luther King Jrâ€™s Speech. The writer conducts this research by using descriptive method. In collecting data, the speech and its history were taken from the book AmericanÂ  speech and other relevant source from internet as a source data. The data analysis was based on by Juez (2008:20) and supportedby De Beaugrande and Dressler (1986:8) and Aarts and Aarts (1982: 4).These discourse analysis norms were applied in the Martin Luther King Jrâ€™s Speech. The theory consists of seven norms, they are: cohesion (pronoun, substitusion, ellipsis, conjuction, and lexical), coherence (mark coherence and unmark coherence), intentionality, acceptability, informatifity, situationality, and intertextuality. The result of this research shows that in the cohesion norm, there are 131 pronouns,Â  52 subtitusion, 1 ellipsis, 90 conjuction and 16 lexical. In coherence norm, there are 46Â  mark coherence and there is no unmark coherence. There are also others norms like intentionality, acceptability, informatifity, situationality, and intertextuality. This speech contains the seven norms sugested by Juez (2008:20). Keywords : Discourse Analysis, Speech, Martin L.King Jr., Norms.